CHARACTER EDUCATION VALUES AS REFLECTED BY GATOTKACA DRESS PROPERTIES IN SURAKARTA PUPPETRY STYLE - Vayoga, Brahmana Rendra; Suyanto, Suyanto; Subiyantoro, Slamet (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2018)
The purpose of this study are: (1) To understand the character of Gatotkaca characters in wayang kulit Surakarta style. (2) To investigate the symbolic meaning of Gatotkaca fashion clothing in Surakarta style puppetry. This study uses qualitative descriptive to present the existing data in the field by way of describing and interpreting. Technique of collecting data is done by interview and direct observation. The results of this study are: (1) Gatotkaca figure represents a humble character, and he has a high spirit of nationalism, (2) Gatotkaca has dress properties such as of Caping Basunanda, Kotang Antra Kusuma, and Trompah Padakacarma which represent as the key values in character education. Gatotkaca’s personal characteristics and his dress property have a deep meaning and values that can be precious for character education.